QUANTITATIV ANALYSIS AND PHARMACOECONOMICS OF ANTIBIOTIC USE IN COMMUNITY-ACQUIRED PNEUMONIA (CAP) IN PKU MUHAMMADIYAH GAMPING - Ayunda Putri Hadiningrat; Akrom -; Risdiana Irma (Universitas Muhammadiyah Magelang, 2021)
Antibiotics are therapies used in cases of infection. Inappropriate use of antibiotics will cause the impact of resistance. Antibiotic use studies need to be done as a step to reduce this impact. The purpose of this study was to determine the practice of using antibiotics by measuring the quantity using the Defined Daily Dose (DDD) and DU90% method in inpatients with a diagnosis of Community-Acquired Pneumonia (CAP) at PKU Muhammadiyah Gamping Hospital. This study is a retrospective study on inpatients of PKU Muhammadiyah Gamping Hospital in 2016-2018. Data was obtained from patient medical records. The results showed a change in the pattern of antibiotic used in 2016-2018. Ceftriaxone and ceftazidime are the most widely used antibiotics. Ceftriaxone with a DDD value of 12.59; 22.49; 23.53 / 100 bed-days and ceftazidime with a DDD value of 17.09; 12.98; 10.59 / 100 bed-days. Antibiotics that are included in DU 90% are Ceftriaxone, Ceftazidime, Cefixime and Levofloxacine. The conclusion of this study is that there is a change in the pattern of antibiotic use in cases of Community-Acquired Pneumonia (CAP) in 2016-2018.